Effects of high-intensity resistance training on extended body composition and functional fitness after spinal cord injury with motor complete paraplegia: a randomized controlled trial study - Kim, Seckjin; Lee, Junmin; Kim, Wonjung; Jin, Seungmo; Bae, Younghyeon; Lee, Hyunjong; Kim, Junghwan; An, Kyungjun; Park, Nohhwan; Shin, Seyoung (Frontiers in Public Health, 2025)
PurposeThis study aimed to compare the effects of high-intensity resistance training (HIRT) versus moderate-intensity resistance training (MIRT) on bone mineral density (BMD), body composition, and functional fitness in individuals with motor-complete paraplegia after spinal cord injury (SCI), and to propose a tailored exercise intervention for this population.MethodsParticipants with motor-complete paraplegia were randomized into HIRT (n = 8) or MIRT (n = 8) groups. Both groups completed an 8-week elastic resistance training program. The measured outcomes included extended body composition (BMD, T-scores, lean mass, and fat mass) and functional fitness components (cardiorespiratory endurance, muscular strength, endurance, and flexibility).ResultsNo significant changes in BMD were observed in either group (p > 0.05). The HIRT group demonstrated significant improvements in lean mass (p < 0.001), chest press strength (p = 0.024), muscular endurance (p = 0.008), and VO₂peak (p = 0.001), while the MIRT group showed no significant changes. Flexibility and fat mass did not significantly differ in either group (p > 0.05).ConclusionHigh-intensity resistance training was more effective than MIRT in improving lean mass and functional fitness in individuals with motor-complete SCI. Although BMD did not change over the 8-week period, its assessment remains clinically relevant, and future studies should investigate longer-duration or higher-intensity protocols to promote skeletal adaptations.